PENGARUH PENDIDIKAN KARAKTER DAN MULTIKULTURAL DALAM MEMBANGUN SIKAP TOLERANSI DAN PERDAMAIAN PADA PESERTA DIDIK - Safara Diniah; Saiful Aziz Al-Falaq; Vania Indah Sabillah; Rijal Maulana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Education has an important role in developing students' interests and talents and improving their quality of life. Character and multicultural education have become very relevant in facing complex global challenges. Character education aims to instil moral and ethical values, while multicultural education emphasises the importance of respect for cultural diversity. This research uses the literature study method to examine the influence of character and multicultural education in building attitudes of tolerance and peace. The results show that character and multicultural education programmes can improve tolerance, empathy and the ability to resolve conflicts constructively among students. Effective implementation of these two approaches is expected to create a young generation that lives harmoniously in diversity and has high social awareness. Keywords: Character Education, Multicultural Education, Tolerance